Implementation of Digester Machine Automation Using an Arduino Uno and Multisensing Sensors to Improve Crude Palm Oil Production Efficiency - Maharani, Putri; Alfisyahrin, A; Syukriyadin, S (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2025)
The production of crude palm oil was highly dependent on the operational efficiency of the digester unit, in which improper control of temperature, material level, and stirring speed often resulted in reduced productivity and unstable operating conditions. This study aimed to address these issues by developing an automated control system to improve digester performance through integrated sensing and motor control. An automation system based on a microcontroller was designed and simulated using multisensing technology, including temperature monitoring within an optimal range of 90–95 °C, material level detection with a minimum threshold of 75%, and direct current motor speed regulation through a motor driver module. System logic and operational behavior were evaluated using Proteus simulation software prior to hardware implementation. The simulation results showed that the proposed system was able to automatically stop the digester motor when the operating temperature exceeded 95 °C or when the material level dropped below the predefined threshold, thereby preventing unsafe operating conditions and potential equipment damage. The automated response ensured more stable digester operation and reduced the risk of process inefficiencies. The overall findings indicated that the proposed low-cost automation system effectively enhanced process control and operational reliability. Furthermore, the implementation of this system demonstrated a potential improvement in production efficiency of approximately 20–30%. These results confirmed that microcontroller-based automation with multisensing integration provided a practical and efficient solution for optimizing digester operations in crude palm oil processing plants.